LALONGÈT Melawan Hegemoni Negara: Potret Perempuan Rural di Jawa dalam Novel Ulid Tak Ingin Ke Malaysia Karya Mahfud Ikhwan - Muhammad Yasif Femi Mifthah; Mu’awal Panji Handoko; Kurniawan Kurniawan (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to explain the description of the ideology of state ibuism in the novel Ulid Tak Ingin ke Malaysia by Mahfud Ikhwan and how the narrative of resistance to it is through the depiction of female characters in the novel. This research uses qualitative and descriptive methods. The results of the research show that the hegemony of the ideology of state ibuism in the novel is represented through the character of Kaswati who plays the role of a good wife and mother in taking care of her husband and children. The resistance to the hegemony of state ibuism represented through the figures of Kaswati, Juwairiyah, and the women of Lerok village. The symbol of resistance carried out by Kaswati and the Lerok women is to leave their main duties as mothers and wives to work in Malaysia. However, behind the narrative of resistance, there is a narrative to return to the ideological symbol that is perceived by the opponents which is marked by the desire of female figures to return to the integrity of the family.